KNOWLEDGE AND PRACTICE OF BREAST SELF-EXAMINATION FOR BREAST CANCER PREVENTION AMONG ADULT NIGERIAN WOMEN RESIDING IN SUNDERLAND, UNITED KINGDOM - Ibrahim, Musa Saulawa; Ochepo, Peter; Udo, Godswill; Sabo, Abdulwali; Abdullahi, Usaini A (FUDMA Journal of Sciences, 2026)
Breast cancer is a major global health concern, significantly contributing to morbidity and mortality among women. Early detection is essential for reducing breast cancer-related deaths, and breast self-examination (BSE) represents a simple and cost-effective preventive strategy. However, the practice of BSE among specific migrant populations remains insufficiently studied. This study evaluates the knowledge and practice of BSE among adult Nigerian women residing in Sunderland, United Kingdom. A cross-sectional study was conducted using a structured questionnaire distributed to 126 Nigerian women aged 18 years and above residing in Sunderland, UK. The questionnaire evaluated participants' knowledge of BSE, frequency of practice, perceived barriers, and factors influencing adherence. Descriptive statistics, including percentages, and inferential analysis using chi-square tests were applied for data analysis. A substantial majority (88.10%) of respondents reported awareness of BSE, with health workers identified as the primary source of information. Participants also demonstrated a high level of BSE practice, with 40.48% performing it weekly. Additionally, a statistically significant association was found between knowledge and practice of BSE in breast cancer prevention among the study population (p < 0.05). The findings highlight the necessity of ongoing education regarding breast cancer prevention strategies. Healthcare professionals are encouraged to intensify awareness initiatives by providing Nigerian women with information on the optimal timing and techniques for performing BSE, thereby improving adherence and early detection outcomes.
Keywords: Knowledge; Practice; Breast Self-Examination; Breast Cancer Prevention; Nigerian Women; Sunderland